2024
DOI: 10.3390/math12040588
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Motion Prediction with Empirical Mode Decomposition-Based Random Vector Functional Link

Asad Rasheed,
Kalyana C. Veluvolu

Abstract: The precise prediction of tumor motion for radiotherapy has proven challenging due to the non-stationary nature of respiration-induced motion, frequently accompanied by unpredictable irregularities. Despite the availability of numerous prediction methods for respiratory motion prediction, the prediction errors they generate often suffer from large prediction horizons, intra-trace variabilities, and irregularities. To overcome these challenges, we have employed a hybrid method, which combines empirical mode dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Here, H represents the concatenation of the hidden layer output features and input nodes via direct links. As earlier explained, the input node directly connected to the output node via direct link does not require assigning any weights as depicted in Figure 1 [30,33,42]. The addition of these direct links in RVFL serves to regularize the model, resulting in improved generalization performance and lower model complexity.…”
Section: Random Vector Functional Link (Rvfl)mentioning
confidence: 99%
See 2 more Smart Citations
“…Here, H represents the concatenation of the hidden layer output features and input nodes via direct links. As earlier explained, the input node directly connected to the output node via direct link does not require assigning any weights as depicted in Figure 1 [30,33,42]. The addition of these direct links in RVFL serves to regularize the model, resulting in improved generalization performance and lower model complexity.…”
Section: Random Vector Functional Link (Rvfl)mentioning
confidence: 99%
“…An independently developed method, the single hidden layer neural network with random weights (RWSLFN), was reported in [29], differing from RVFL by excluding the direct links. Research has shown that the direct links significantly enhances RVFL's performance, especially in time series forecasting [27,[30][31][32][33]. In [16,31,33], the authors clearly demonstrated that the presence of the direct links in RVFL help to regularize the randomization and reduce the model complexity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation